2014
DOI: 10.12659/aot.890821
|View full text |Cite
|
Sign up to set email alerts
|

Intention of Donors to Re-Donate Livers after Living Donor Liver Transplantation in a Liver Transplant Center in Asia

Abstract: Factors associated with a willingness to re-donate included first-degree relatives of the recipient, donor satisfaction with the donation process, and recipient complications. This study not only showed the safety of liver donation, but also had a positive effect on the intention to re-donate to enhance motivation for liver donation and increase the recruitment of living liver donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Moreover, Bhatti et al [32] showed that acceptable post-donation QoL was achieved and no significant difference in scores was observed between donors with and without surgical complications. This report is similar with those of Beavers et al [33], who reported that regardless of recipient outcome, 100% of donors would donate again and of Chang et al [34] who reported that 87% of donors showed a willingness to re-donate. In contrast, Kousoulas et al [35] reported that donors did not regret their decision to donate but development of postoperative donor complications and the postoperative recipient mortality had a negative effect on the Health-related QoL of donors.…”
Section: Quality Of Lifesupporting
confidence: 90%
“…Moreover, Bhatti et al [32] showed that acceptable post-donation QoL was achieved and no significant difference in scores was observed between donors with and without surgical complications. This report is similar with those of Beavers et al [33], who reported that regardless of recipient outcome, 100% of donors would donate again and of Chang et al [34] who reported that 87% of donors showed a willingness to re-donate. In contrast, Kousoulas et al [35] reported that donors did not regret their decision to donate but development of postoperative donor complications and the postoperative recipient mortality had a negative effect on the Health-related QoL of donors.…”
Section: Quality Of Lifesupporting
confidence: 90%
“…Sixty-seven unique studies, including 3 conference abstracts, met our inclusion criteria. 6-8,21-75 Fifty-three articles compared surgical outcomes between RL and LL donors and 31 between RL- and LL-LDLT recipients. Included studies were conducted mostly in Asia (n = 52, 77.6%), with few reports from Europe (n = 9, 13.4%) and the Americas (n = 5, 7.5%).…”
Section: Resultsmentioning
confidence: 99%
“…22,23,26-32,37,39-41,44-46,49,59,63,65,66,73,74 All remaining 4 studies had scores between 5 and 7 and were classified as of moderate quality. 6-8,24,25,33-35,38,42,43,47,48,50,51,53-58,60-62,64,67-72,75 Publication bias was evaluated for 6 meta-analyses including ≥10 studies ( Figure S1, SDC , http://links.lww.com/TP/C459). Asymmetry was only identified for the donor bile leak meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al had a similar observation in their study in which they found the majority were motivated to donate again. Close relations, donor satisfaction and recipient complications were the factors associated with a willingness to redonate 25 . These factors if taken into consideration can help to enhance the pool of liver donors.…”
Section: Discussionmentioning
confidence: 99%
“…complications were the factors associated with a willingness to redonate. 25 These factors if taken into consideration can help to enhance the pool of liver donors. Parolin et al also concluded that donation had changed the lives of donors and would consider donating again hence donor safety and quality of life should remain the priority.…”
Section: N (%)mentioning
confidence: 99%